Neoadjuvant chemotherapy of invasive bladder cancer - S. N. Isayeva; S. P. Selivanov; Ye. V. Udut; Т. А. Kovalik; T. I. Shabunina (Бюллетень сибирской медицины)
A total of 40 chemonaive patients with invasive transitional cell carcinoma received gemcitabine 2 400 mg/m2 on days 1, 8 and 15 plus cisplatin 100 mg/m2 on day 2 as a presurgery treatment. Cisplatin in a single dose of 20 mg/m2 administered into pubic. Grade 3 hematologic toxicity was in 27,5% of patients. The effectiveness of neoadjuvant chemotherapy was 73%.